The role of social media in mobilizing political protest: evidence from the Tunisian revolution - Anita Breuer (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
One of the hallmarks of the Tunisian uprising that ousted President Zine el-Abidine Ben Ali in January 2011 was its broad base of support. To the surprise of many Middle East experts who had previously regarded co-opted and quiescent middle classes as the bedrock of stability for authoritarian regimes in the region, the Tunisian revolution rode on the back of a broad coalition of social forces that united an alienated intellectual elite with the rural poor and urban middle classes in opposition to the regime. It is a widely shared assumption that this joining of disparate forces would not have been possible without modern communication technologies and social media. But it is less clear exactly how such social media interacted with other contextual factors to bring about a national protest movement of sufficient proportions to topple an extremely entrenched authoritarian regime. Drawing on evidence from the popular protests in Tunisia between December 2010 and January 2011, expert interviews with Tunisian bloggers, and a web survey conducted among Tunisian Facebook users, this paper argues that social media (1) allowed a “digital elite” to form personal networks and circumvent the national media blackout by brokering information for outside mainstream media; (2) helped to overcome the “free rider” problem of collective action by reporting the magnitude of protest events; and (3) facilitated the formation of a national collective identity which was supportive of protest action and transcended geographical and socio-economic disparities by providing a shared, mobilizingelement of emotional grievance.
Keywords: 330; Demokratie und Autokratie; Technologie und Innovation